Ivonescimab for EGFR-mutant lung adenosquamous carcinoma after multiline therapy: A case report - Pan, Xiaohua; Zhang, Jianya; Ye, Chao; Zhu, Wanhui; Qu, Wenshu (Frontiers in Oncology, 2025)
This case report describes a 51-year-old male with advanced Epidermal Growth Factor Receptor (EGFR) mutant (p.T790M and p.L858R) lung adenosquamous carcinoma who achieved a rapid partial response (PR) to ivonescimab monotherapy following progression on multi-line therapies, including third-generation EGFR-tyrosine kinase inhibitors (EGFR-TKIs), platinum-based chemotherapy, anti-angiogenic therapy, and immune checkpoint inhibitors. Despite initial responses to first-line firmonertinib-based combination therapy, progression-free survival (PFS) 13 months, the patient developed sequential resistance to subsequent regimens, including liver/brain metastases and treatment-related toxicities. After fourth-line therapy failure and severe intolerance to albumin-bound paclitaxel and bevacizumab, two cycles of ivonescimab—a first-in-class programmed cell death protein receptor-1 (PD-1)/vascular endothelial growth factor-A (VEGF-A) bispecific antibody—induced significant regression of pulmonary target lesions (PR), sustained over six cycles with minimal toxicity. This case highlights ivonescimab’s dual-mechanism potential to overcome resistance in EGFR-mutant Non–small cell lung cancer (NSCLC) by concurrently alleviating PD-1-mediated immunosuppression and VEGF-driven angiogenesis. The observed efficacy in a low PD-L1 expression, tumor proportion score (TPS) 5%, tumor protein 53 (TP53)-co-mutated, and adenosquamous histology context aligns with prior clinical trial data (HARMONi-A/2), suggesting broad applicability across heterogeneous subgroups. While the rapid PR and favorable safety profile are promising, longer follow-up is required to assess durability and survival benefits. These findings underscore the need for further investigation of bispecific antibodies in precision oncology paradigms for multi-refractory EGFR-driven NSCLC.